Incidence of hepatitis C virus infection in Italian patients with idiopathic pulmonary fibrosis. Issue 3 (March 1996) - Meliconi, R; Andreone, P; Fasano, L; Galli, S; Pacilli, A; Miniero, R; Fabbri, M; Solforosi, L; Bernardi, M
Abstract : BACKGROUND: A viral cause of idiopathic pulmonary fibrosis (IPF) was recently suggested by a Japanese study in which a high prevalence of anti-hepatitis C virus (HCV) antibodies was detected. A subsequent British study failed to confirm these results. METHODS: Antibodies to HCV were evaluated in 60 patients with IPF, 130 patients with non-interstitial lung disease, and in 4614 blood donors. HCV-RNA and HCV genotypes were evaluated in the anti-HCV positive patients with IPF. Anti-HCV antibodies were evaluated by ELISA and confirmed by recombinant immunoblotting assay (RIBA). HCV-RNA and genotypes were detected by reverse transcriptase polymerase chain reaction (PCR). RESULTS: Eight patients with IPF had anti-HCV antibodies detected by ELISA (13.3%). In the blood donor control group the prevalence of HCV antibodies was lower (0.3%). In patients with non-interstitial lung disease HCV antibody prevalence was 6.1%. In all eight patients with IPF found to be anti-HCV positive by ELISA, HCV antibodies were also detected by RIBA. Furthermore, all were HCV-RNA positive by PCR assay. HCV genotypes were identified in four of these eight patients. In all four genotype II was present and in two it was associated with genotype III and/or genotype IV. In the remaining four cases the genotype was not identified. CONCLUSION: Italian patients with IPF show an increased prevalence (approximately 13%) of HCV infection and viral replication, but the prevalence of anti-HCV antibodies does not differ from other lung diseases.